ANALISIS KOMPARATIF PARADIGMA BEHAVIORISME DAN KONSTRUKTIVISME DALAM PEMBELAJARAN - Sabrun Jamil; Hesti Rahmawati; Mutiara Haya Afifah; Natasya Amelia Loviana; Yuniy Sarah Hasibuan (STKIP Subang, 2026)
This research presents a comparative analysis of the behaviorist and constructivist paradigms in the context of teaching and learning. The study was conducted in response to the increasing need for learning approaches that effectively address the demands of twenty-first-century education. Its primary objective is to explore the characteristics, differences, strengths, limitations, and educational implications of both paradigms. A qualitative literature review was employed as the research method by analyzing relevant books, scholarly articles, and other credible academic references. The findings reveal that the behaviorist paradigm emphasizes learning as a process of observable behavioral change through stimulus, response, reinforcement, and repeated practice, making it particularly suitable for developing fundamental skills and disciplined behavior. Conversely, the constructivist paradigm views learners as active participants who construct knowledge through experience, interaction, inquiry, and reflection, thereby fostering critical thinking, creativity, collaboration, and problem-solving abilities. The study concludes that both paradigms offer valuable contributions to educational practice. Integrating the structured principles of behaviorism with the learner-centered approach of constructivism can support the creation of more effective, meaningful, and balanced learning experiences that align with the goals of contemporary education.